- #1

- 143

- 0

v(t)=1 where 0=<t<+infinity

v(t)=0 otherwise

I applied the general definition relation for FT:

v(w)=integral(v(t)*e^-jwt) ; - infinity<t<+infinity

but i had v(w)=infinity due to the term infinity-displaced e^(+jwt) so that's wrong of course!

I think we could divide this function into two functions for example:

v'(t)=1/2 ; t of all values

v''(t)=1/2 ; 0=<t<+infinity

v''(t)=-1/2; -infinity<t<0

so we notice v(t)=v'(t)+v''(t)

I don't know what to do , could anyone help!

thanks!